Action research supported by remote collaboration tools: analysis of two operations management applications - de Souza, João Paulo Estevam; Muniz, Jorge [UNESP] (FapUNIFESP (SciELO), 2023)
Paper aims: This paper aims to discuss how Remote Collaboration Tools (RCT) can support and contribute to Action Research (AR) applications in operations management research. Originality: Researchers shall capture the complexity of studied phenomena when conducting AR. Although, there is a lack of information regarding the use of RCT in AR. Hence, this paper provides original and comprehensive guidelines for the application of RCT in AR. Research method: This paper provides an ex-post analysis of two face-to-face AR cases, based on the steps proposed by Coughlan and Coughlan (2002). Based on the ex-post analysis, it explains ex-ante and how RCT can impact and contribute to AR on operations management. Main findings: The paper presents reflections, insights and guidance about the impacts of RCT in AR. RCT allow possibilities for continuity and efficient use of resources in AR. Although, when choosing RCT, special efforts should be put into team building and engagement. Implications for theory and practice: The description of how the RCT can be used in the AR cycle can contribute to theory based on empirical results as guidance to increase value considering AR quality criteria. We intend to provide material for the advance of the field of Operations, Production and Management, theoretically and practically.
Keywords: Collaboration; Digital tools; Production; Remote work; Research method